Journal of Human Sport and Exercise - 2019 - Summer Conferences of Sports Science 2019
DOI: 10.14198/jhse.2019.14.proc5.45
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of green creativity in the relationship between proactive green innovation, reactive green innovation and the performance of Green product development: A case of Thai sports manufacturing firms

Abstract: The study is carried out to examine the mediating role of green creativity in the relationship between proactive green innovation, reactive green innovation and the performance of Green product development. The study has used the survey-based methodology to achieve the research objectives. The SEM-Pls is used to analyse the data collected from the manufacturing firms in the Thai Sports industry. For the cumulative green activity Some managerial mediations like reimbursement plans, brainstorming competitions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…The results showed that green creativity has a positive and significant effect on brand performance. This finding is consistent with Wu [26], Chen et al [23], Boso et al [41], Aeknarajindawat and Jermsittiparsert [40] and Ferreira et al [43]. To explain this finding, it can be claimed that brand performance will be improved if company employees propose new ways to achieve environmental goals, suggest new green ideas to improve environmental performance, promote new green ideas to others, develop good plans for implementing green ideas, and come up with creative solutions to environmental issues.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The results showed that green creativity has a positive and significant effect on brand performance. This finding is consistent with Wu [26], Chen et al [23], Boso et al [41], Aeknarajindawat and Jermsittiparsert [40] and Ferreira et al [43]. To explain this finding, it can be claimed that brand performance will be improved if company employees propose new ways to achieve environmental goals, suggest new green ideas to improve environmental performance, promote new green ideas to others, develop good plans for implementing green ideas, and come up with creative solutions to environmental issues.…”
Section: Discussionsupporting
confidence: 78%
“…Studies that have examined the relationship between corporate social responsibility and commitment have shown that there is a positive and significant relationship between corporate social responsibility and commitment [35][36][37][38][39]. In addition, research has shown that there is a positive and significant relationship between creativity and performance [40][41][42][43][44]. Therefore, it is assumed:…”
Section: Corporate Social Responsibility Green Creativity and Performentioning
confidence: 99%
“…Creativity culture shapes an atmosphere that is conducive to enhance environmental commitment of any business activities and reduce detrimental impact on the environment (Aeknarajindawat & Jermsittiparsert, 2019;W. Song, Wang, et al, 2020).…”
Section: Green Creativity and Environmental Performancementioning
confidence: 99%
“…Chen & Chang, 2013). Creativity culture shapes an atmosphere that is conducive to enhance environmental commitment of any business activities and reduce detrimental impact on the environment (Aeknarajindawat & Jermsittiparsert, 2019; W. Song, Wang, et al, 2020). So we hypothesized the following:H5 Green creativity and environmental performance are positively related.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Competitive advantage is obtained by high level of creativity (Basheer et al, 2019). According to Aeknarajindawat & Jermsittiparsert (2019), green creativity has a crucial role for the performance improvement of the organization. A number of scholars have conducted studies related to green creativity and business performance.…”
Section: Introductionmentioning
confidence: 99%